Implementation of the Maqashid Syariah Index Approach on the Performance of Sharia Regional Development Banks in Indonesia - Muhamad Yusup; Dewi Sartika Nasution (Journal of Finance and Islamic Banking, 2020)
The implementation of sharia bank performance appraisal models has so far adopted the conventional banking model in terms of evaluating financial performance. Based on this phenomenon, the evaluation of sharia banking performance should use performance measurement based on the maqashid sharia method. The Maqashid Syariah Index (MSI) method has three main objectives, including tahzibal-fardi (educating people), iqamah al-â€˜adl (upholding justice), and jalbal-maslahah (public interest). The research is a quantitative descriptive study, to explain the maqashid syariah index ratio in analyzing the performance of sharia regional development banks in Indonesia. The sample used in the study using purposive sampling. The performance of sharia regional development banks based on the maqashid sharia index approach illustrates that sharia regional development banks in Indonesia in their implementation of sharia operations are more dominant in the goals of Iqmah al-Adl, meaning that regional development banks in Indonesia are more concentrated in terms of applying sharia principles. The sharia regional development bank in Indonesia that has achieved the best performance according to the Maqashid Syariah Index approach is the Aceh Syariah Bank.Â